(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
It was designed and implemented an electromechanical system controlled by keyboard for controlling the growth parameters of semiconductor films such as ZnO and ZnSe on glass substrates. The parameters that can be controlled by keyboard are time and sequence of the immersion in the solutions, and the number of cycles. The SILAR system is autonomous, versatile, with control measures such as temperature. Microcontrollers have been used to fit the electromechanical system and stepper motors place the sample holder in the respec-tive solutions, the information of the control parameters is displayed on a display. The results obtained in the growth of semiconductor films indicate that the automated system SILAR has a high performance for obtaining a homogeneous sample with thicknesses controlled by the number of cycles. This system reduces costs, time and gets better control over the parameters used in different applications.